2004
DOI: 10.1161/01.cir.0000127129.94129.6f
|View full text |Cite
|
Sign up to set email alerts
|

Non–Polymer-Based Paclitaxel-Coated Coronary Stents for the Treatment of Patients With De Novo Coronary Lesions

Abstract: ; for the DELIVER Clinical Trial InvestigatorsBackground-Paclitaxel, a microtubule-stabilizing compound with potent antitumor activity, has been shown to inhibit smooth muscle cell proliferation and migration. The DELIVER trial was a prospective, randomized, blinded, multicenter clinical evaluation of the non-polymer-based paclitaxel-coated ACHIEVE stent compared with the stainless steel Multi-Link (ML) PENTA stent. Methods and Results-A total of 1043 patients with focal de novo coronary lesions, Ͻ25 mm in len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(82 citation statements)
references
References 40 publications
2
72
0
8
Order By: Relevance
“…As showed in the DELIVER I study (Cook Incorporated, USA; Guidant Corporation), highdose paclitaxel delivery through nonpolymer-based stents resulted in a significant inhibition of neointima proliferation; however, this reduction did not translate into a sufficient decrease of targeted vessel failure and ISR (Table 1) (133). The TAXUS program (Boston Scientific, USA) employs a polymer coating that provides biphasic drug release, with an initial burst of paclitaxel release in the first two days, followed by low-level release lasting for the next 10 days.…”
Section: Paclitaxelmentioning
confidence: 99%
“…As showed in the DELIVER I study (Cook Incorporated, USA; Guidant Corporation), highdose paclitaxel delivery through nonpolymer-based stents resulted in a significant inhibition of neointima proliferation; however, this reduction did not translate into a sufficient decrease of targeted vessel failure and ISR (Table 1) (133). The TAXUS program (Boston Scientific, USA) employs a polymer coating that provides biphasic drug release, with an initial burst of paclitaxel release in the first two days, followed by low-level release lasting for the next 10 days.…”
Section: Paclitaxelmentioning
confidence: 99%
“…In coronary arteries, however, excessive formation of neointima has been successfully inhibited by the implantation of drug-eluting stents, providing a platform for sustained drug release, which is believed to be a precondition of successful restenosis inhibition (27). Their implementation in clinical practice has however disclosed unexpected long-term results due to the delay in healing accompanied by the risk of late stent thrombosis (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…1,2) The DELIVER trial using the ML PENTA stent reported good clinical and angiographic results; target vessel failure (death, Q-wave or non-Qwave myocardial infarction, target lesion revascularization) was 14.5% at 9 months and stent binary restenosis was 20.6% at 8 months. 1) In the present study, although 46 (54%) patients had diabetes mellitus and the ACC/AHA lesion characteristics of the stented lesion were all B2 or C, the rate of target lesion revascularization was 18.6% and the rate of cardiac events was 24.4% at 9 months. We previously reported on the angiographic restenosis rates of the Palmaz-Schatz (PS) stent (Cordis Corporation, Miami, Florida) and ACS ML stent (Guidant Corporation, Santa Clara, California).…”
Section: Clinical and Angiographic Outcomes After Coronary ML Penta Smentioning
confidence: 99%
“…1,2) The present study was designed to evaluate the clinical (9-month) and angiographic (6-month) results of the ML PENTA stent in complex coronary lesions (modified American College of Cardiology/American Heart Association (ACC/AHA) lesion type B2 or C) 3,4) and to determine independent factors correlated with target lesion revascularization.…”
mentioning
confidence: 99%